Optimized reprocessing of documents using stored processor state - Ollis, James A.; Brailsford, David F.; Bagley, Steven R. (2010)
Variable Data Printing (VDP) allows customised versions of material such as advertising flyers to be readily produced. However, VDP is often extremely demanding of computing resources because, even when much of the material stays invariant from one document instance to the next, it is often simpler to re-evaluate the page completely rather than identifying just the portions that vary.